KUALITAS PELAYANAN PAJAK REKLAME PADA DINAS PENDAPATAN DAERAH KOTA PONTIANAK - Sri Purna Indriaty E.21111115 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
Quality of service is one of the significant variables in the implementation of penal duties or tasks of public services . In the era of regional autonomy in the conduct of affairs in which the authority of government , especially public services that have been provided to the local demands of each region are competing to improve the system of public services the local level . There are still many violations encountered installation of billboards that happens in the area of administrative Pontianak city and become part of the ministry of its own duty to resolve the issue so that taxpayers are aware of the taxes and regulations . The focus of this article is the quality of service of advertisement tax regulations still violate the installation of billboards in the service part of the Regional Revenue Office Pontianak . The results of this study indicate that there are four factors that affect the quality of service of advertisement tax is the tax system still violates the rules installation of billboards , the limited human resources as the officer who executes advertisement that violates the rules , Revenue strategy in addressing customers who default installation of billboards , and customer feedback as a taxpayer regarding the services provided to the taxpayer Revenue advertisement . Element in the implementation of this Pontianak City Revenue Office , in order to increase human resources and other support facilities in the handling of billboards that violate the rules . Keywords : System Services , Human Resources , Strategy , Customers.